Publisher Correction: Suppression of insulin feedback enhances the efficacy of PI3K inhibitors. (15th November 2018) - Hopkins, Benjamin; Pauli, Chantal; Du, Xing; Wang, Diana; Li, Xiang; Wu, David; Amadiume, Solomon; Goncalves, Marcus; Hodakoski, Cindy; Lundquist, Mark; Bareja, Rohan; Ma, Yan; et al.
In this Letter, author Xing Du was incorrectly listed as Du Xing; this has been corrected online.